ANXIETY OF J.T.SANBORN IN THE HURT LOCKER MOVIES DIRECTED BY KATHRYN BIGELOW (2008): A PSYCHOANALYTIC APPROACH - WIJAYANTI, TRISKA NORMALIA (2011)
The problem of the study is to reveal how the major character reflects his anxiety. The objective of the study is to analyze the film based on structural analysis and based on the psychoanalytic analysis. This study is descriptive qualitative study. The object of the study is The Hurt Locker movie directed by Kathryn Bigellow and written by Mark Boal published in 2008 in Italy by Warner Bros. The data sources are divided into two namely primary and secondary data source. The primary data source is the film itself and the secondary data source is the other source is the other source related to the analysis such as references, author biography, criticisms relation to the problem and material related to the study whether picking up from books or internet. The methods of data collection are observation and library research. The technique of data analysis is descriptive analysis. The results of the study are as follows. First, based on the structural analysis, Kathryn Bigellow delivers a moral message that the soldiers must survive their live for the against with the anxious when in the war. And second based on psychoanalysis, the writer concludes that the problem of the major character cause the conflict of his mental condition. It happens when there is contradiction between Id, Ego, and Superego and it brings him into anxiety